2013
DOI: 10.1007/s00167-013-2680-z
|View full text |Cite
|
Sign up to set email alerts
|

Tendon healing: an overview of physiology, biology, and pathology of tendon healing and systematic review of state of the art in tendon bioengineering

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 52 publications
2
92
0
6
Order By: Relevance
“…In addition, due to the surgical trauma of the ACL reconstruction and therefore the presence of growth factors, healing of the meniscus and its insertion (if avulsed) might be induced and result in "fixation by healing" [36][37][38]. Also the MFL which prevents dislocation to a certain extend was present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the surgical trauma of the ACL reconstruction and therefore the presence of growth factors, healing of the meniscus and its insertion (if avulsed) might be induced and result in "fixation by healing" [36][37][38]. Also the MFL which prevents dislocation to a certain extend was present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that IGF-1 has an important role in tendon repair and tissue regeneration by mean of tenocyte migration and division, matrix expression and collagen synthesis. 3,4 Dahlgren et al 13 reported that administering IGF-I exogenously during the first 2 weeks following injury provided a therapeutic effectiveness by bolstering low endogenous tissue levels and enhancing the metabolic response of individual tendon fibroblasts. In this study, we attempted to transfect wounded rat Achilles tendons with IGF-1 plasmid DNA using UTMD to enhance tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…3 Tissue growth factors can regulate cell proliferation, migration of fibroblasts, differentiation and matrix synthesis and have the potential to directly influence cellular mitogenesis, thus having an important role in tendon repair. [3][4] Insulin-like growth factor-1 (IGF-1) induces tenocyte migration and division, matrix expression and collagen synthesis, thus having the potential to enhance wounded tendon regeneration. 4 Many studies 5 have demonstrated that IGF-1 can promote tendon repair and enhance wounded tendon regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O papel do processo inflamatório, as modificações histopatológicas e a patogênese da lesão crônica do tendão não estão completamente entendidos. Sabe-se que quando o tendão é posto em sobrecarga ele perde a sua capacidade reparadora basal podendo levar à micro traumas cumulativos que enfraquecem as ligações do colágeno, a matriz não-colágena e os elementos vasculares do tendão 3 . Diversos recursos terapêuticos como Laser 4,5 , Led e ultrassom terapêutico isolado 6,7 , combinados à fármacos e fitoterápicos 6,8 por meio da sonoforese tem sido utilizados na inflamação e reparo de tendão.…”
Section: Introductionunclassified